How Does Irrigation with Wastewater Affect the Physical Soil Properties and the Root Growth of Sugarcane under Subsurface Drip? - Oswaldo Palma Lopes Sobrinho; Leonardo Nazário Silva dos Santos; Marconi Batista Teixeira; Frederico Antônio Loureiro Soares; Ivo Zution Gonçalves; Eduardo Augusto Agnellos Barbosa; Aline Azevedo Nazário; Edson Eiji Matsura; Luciana Cristina Vitorino; Mateus Neri Oliveira Reis; Layara Alexandre Bessa (Agronomy, 2024)
Studies on the development of the root system can provide important information about responses to different management strategies, such as the use of lower quality water, also evaluating the interaction between plants and the physical properties of the soil. This study tested the hypothesis that irrigation with treated sewage effluent (TSE) supplies the water needs of sugarcane plants, increasing root growth and improving the physical properties of the soil. We evaluated the effects of subsurface dripping with TSE or surface reservoir water (SRW) on the root development of first ratoon cane (Saccharum officinarum L.) and the physical properties of dystrophic red latosol. Irrigation treatments were applied at 20 and 40 cm and soil properties were evaluated at soil depth layers of 0–20, 20–40, 40–60, and 60–80 cm. We verified that under irrigation with TSE and SRW, shallower soil layers present better porosity, soil aggregation, and aggregate stability conditions, parameters that improve the root system development and plant growth. On the other hand, deeper soil layers have lower macroporosity and higher total clay volume, indicating the possibility of compaction and greater limitations for sugarcane root growth. These results are important for understanding soil quality and provide significant information for agricultural management and for the implementation of sustainable soil conservation practices. This study shows the efficiency of TSE as an alternative water source for sugarcane crops.